(untitled) (Eurasian Research Bulletin, 2022)
The article analyzes the importance of using bilutleie technologies in the implementation of hierarchical preparation of Engineers. It has been studied that cloud technology in education can provide access to a wider range of forms and methods of teaching, as well as one of the modern methods of intensification and optimization of the learning process.